Aggregating group MCDM problems using a fuzzy Delphi model for personnel performance appraisal - Anisseh, Mohammad; Mohd Yusuff, Rosnah; Shakarami, Alireza (Academic Journals, 2009)
Personnel performance appraisal is a tool towards achieving organization goals. Its main focus is to in-crease the abilities, merits and growth of personnel. We looked at the personnel performance appraisal as an element of group decision making model in which personnel are evaluated from different points of view. A fuzzy Delphi method and linguistic terms represented by triangular fuzzy numbers were applied to bring out qualitative and quantitative attributes and assess attributes weights and relative importance of evaluation group’s viewpoints. We developed MCDM models for group personnel performance appraisal. All the known MCDM methods have their own advantages and drawbacks and there-fore yield different results based on their various techniques. As a consequence, we presented a model for aggregation of the results of MCDM models.